REMEDIASI MISKONSEPSI MENGGUNAKAN METODE INTERACTIVE PROBLEM TASK AND EXPERIMENT BERBANTUAN LABINAPP TENTANG GETARAN DI SMP - Lintang, Ari; Sahala Sitompul, Stepanus; Mursid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aims to determine the effectiveness of interactive Problem task and Experiments (P&E) method simulated by LabInApp to reduce students? misconception on oscillation material at SMP Santo Fransiskus Asisi Pontianak. The research design was one group pretest-posttest design. A total of 32 students were assigned as samples by purposive sampling technique. The data collected using multiple choise diagnostic tests with an open reason. Data analysis through DQM test found that students misconception of 32,8%, 46,9%, 60,0%, 37,5%, 35,5%, 34,9% and 32,9% with medium category. Based on the Mc Nemar test obtained price ?2count of 13.067; 5,882; 11,077; 16,056; 11,077; 4,900; 11,077; 12,071; 17,053; 14,063; 6,750; 6,125; 7,111; and 7,111. Overall price ?2count> ?2table = 3,841 with ? = 5%. Thus, there is a significant change in student misconception. The Wilcoxon Match Pairs test is used to test the effectiveness of interactive problem task and experiment methods. Wilcoxon Match Pairs test results obtained price zcount = -3.7973 and ztabel = 1.96 with ? = 5%. These results indicate that interactive problem task and experiment method effectively decrease student misconception.Keywords: Remediation, misconception, interactive P&E method, simulation LabInApp, oscillation